A Study Relation Emotion Social Security–Economy, Social-Economy Status on Quality of Life Persons (Case Study: Ahwaz City) - alihossein hosseinzadeh; tahereh ahmadipour; elaheh mavalizadeh (توسعه اجتماعی)
This study is aimed to assessing Relation Emotion social security–economy, social–economy subjective and objective status on quality of life in Ahwaz city.  In this research suggests that, emotion social security–economy, social-economy status result different levels quality of life. Then structure of the studies is taken of concept theory, Ideology, method knowledge, Structural approaches. Research data are chosen by survey method from samples with 385 person which are selected by cluster sampling from ahwaz citizens in different steps and gathered. Steps of statistical was done by Spss v 16 software. Result show that, emotion social security–economy, social–economy status are positive effective on quality of life.